QSAR model and microscopic mechanism analysis of dye removal by coagulation of aluminum chloride under alkaline conditions - Zhang, Meilan; Qin, Shengnan; Tan, Yujia; Shen, Zhemin (Frontiers in Environmental Science, 2023)
Introduction: The inorganic coagulant AlCl3 is used in the traditional coagulation method for the decolorization of industrial dye wastewater. We studied its effectiveness in 41 kinds of dye with different structures, including azo, anthraquinone, arylmethane, and indigo dyes. Discussion: The optimal conditions for the removal of dye in the AlCl3 coagulation system were alkaline > neutral > acidic conditions. Under alkaline conditions, the hydrolysis colloid of AlCl3 is positively charged and easily combined with negatively charged anionic dyes by electrostatic adsorption. Therefore, the relationships between the dye removal behavior and molecular parameters under alkaline conditions were analyzed. Methods: Quantitative structure–activity relationship (QSAR) models were built for the color removal rates (Rexp) of 41 dyes and 46 molecular parameters computed by the density functional theory (DFT). Internal validation, external validation, statistical tests, Y-randomization, and applicability domain tests indicated that the optimal models are stable, accurate, reliable, and predictive. Results: The optimal QSAR model showed that surface area (approx.) (SAA) and molecular weight (MW) are two key molecular parameters. Moreover, electrostatic forces and hydrogen bonding are the predominant adsorption forces in this coagulation process.